Appendices for "State power and governance in early imperial China" - Tong, Chun Fung (Universitätsbibliothek Heidelberg, 2023)
Tong, Chun Fung, State power and governance in early imperial China: the collapse of the Qin Empire, 221–207 BCE, Albany: State University of New York Press, 2024
Additional material, the appendices will not be published in the book